2004
DOI: 10.1094/mpmi.2004.17.7.749
|View full text |Cite
|
Sign up to set email alerts
|

RCH1, a Locus inArabidopsisThat Confers Resistance to the Hemibiotrophic Fungal PathogenColletotrichum higginsianum

Abstract: When challenged with the crucifer pathogen Colletotrichum higginsianum, Arabidopsis thaliana ecotype Columbia (Col-0) was colonized by the fungus within 2 to 3 days, developing brown necrotic lesions surrounded by a yellow halo. Lesions spread from the inoculation site within 3 to 4 days, and subsequently continued to expand until they covered the entire leaf. Electron microscopy confirmed that C. higginsianum is a hemibiotroph on Arabidopsis, feeding initially on living cells as a biotroph before switching to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
113
2
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(119 citation statements)
references
References 70 publications
1
113
2
2
Order By: Relevance
“…Development of CLO3-and a-DOX1-Positive Oil Bodies in Perilesional Areas of Leaves Infected with C. higginsianum Infection of C. higginsianum, which is pathogenic to Arabidopsis (Narusaka et al, 2004;O'Connell et al, 2004), resulted in the formation of lesions on leaves 4 d after infection. CLO3 mRNA began to accumulate 4 d after infection with C. higginsianum, and the levels increased significantly within 7 d ( Fig.…”
Section: Identification Of A-dox1 As An Oil Body-localized Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of CLO3-and a-DOX1-Positive Oil Bodies in Perilesional Areas of Leaves Infected with C. higginsianum Infection of C. higginsianum, which is pathogenic to Arabidopsis (Narusaka et al, 2004;O'Connell et al, 2004), resulted in the formation of lesions on leaves 4 d after infection. CLO3 mRNA began to accumulate 4 d after infection with C. higginsianum, and the levels increased significantly within 7 d ( Fig.…”
Section: Identification Of A-dox1 As An Oil Body-localized Proteinmentioning
confidence: 99%
“…Recently, the genus Colletotrichum genome and transcriptome were analyzed (O'Connell et al, 2012). An isolate of Colletotrichum higginsianum has been reported to infect Arabidopsis (Arabidopsis thaliana; Narusaka et al, 2004;O'Connell et al, 2004). The use of model plants enabled the characterization of the interaction between the fungus and Arabidopsis plants in the infected area (Narusaka et al, 2009;Hiruma et al, 2010Hiruma et al, , 2011.…”
mentioning
confidence: 99%
“…Isolates of Colletotrichum higginsianum infect Arabidopsis (O'Connell et al, 2004;Narusaka et al, 2004), which provides a new model pathosystem between Arabidopsis and Colletotrichum in which both partners in the interaction can be genetically manipulated. We previously reported that nonhost resistance of Arabidopsis against Colletotrichum species largely depends on preinvasion immune responses that act at the cell periphery (Shimada et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 1.2 K potential biotic and abiotic stressrelated genes were selected from the genes covered by the Arabidopsis 7 K array (RIKEN, Japan) and Arabidopsis oligo microarray (Agilent Technologies, USA) for this study (Seki et al 2002;Narusaka et al 2003a;2003b;2004a;2004b;. To gain further information on the characterization of plant activators in the defense response, we studied their effect on the expression of the 1.2 K stress-related genes in our microarray.…”
mentioning
confidence: 99%
“…Full-length cDNA microarray analysis was carried out essentially as reported previously (Seki et al 2001;Narusaka et al 2003a;2003b;2004a;2004b;. Arabidopsis wild-type plants (ecotype Columbia; Col-0) were grown in soil for 28 days in a growth chamber at 22°C under a 12-h light/12-h dark cycle.…”
mentioning
confidence: 99%